Farmers' income from oilseeds production in India: Trends and prospects: FARMERS' INCOME FROM OILSEEDS PRODUCTION IN INDIA: TRENDS AND PROSPECTS - PURUSHOTTAM SHARMA (Journal of Oilseeds Research, 2018)
Oilseeds are of pivotalsignificance in the agricultural economy ofIndia supporting income ofmillions offarmers practicing mainly rainfed cultivation. Profitability of oilseeds is an important concern for enhancing domestic production in order to reduce import dependence for edible oils. The present study attempts to analyze the trends in real income from oilseed crops in selected states and discuss some of the underlying factors using secondary data from the cost of cultivation surveys for selected states during the period 2000-01 to 2014-15. Farm income from oilseeds has increased in the states with higher proportionate rise in price realized and or yield of the crop as compared to the change in cost ofinputs. Profitability of oilseeds has declined in the states with higher proportionate increase in cost of inputs as compared to the yield or decline in the real price received. The factors which affected change in income from oilseeds included change in yield realized, farmers' price and change in cost of inputs. There exists a large yield gap for oilseeds across states on account of poor adoption of production technologies and lower application of productive and protective inputs. The yield gap can be narrowed down through ensuring quality input supply at affordable prices, increase adoption of production technology and price support with effective procurement. Efforts are to be enhanced to improve water use efficiency through protective irrigation, effectiveness of extension services to enhance productivity and profitability, and in turn farmers' income.